Concepts of physical fitness active lifestyles for wellness - Corbin, Charles B. (McGraw-Hill Higher Education, 2011)
Lifestyles for health, wellness, and fitness -- An introduction to physical activity -- The physical activity pyramid -- Physical activity : special considerations -- Nutrition and body composition -- Stress management -- Making informed choices